Enhancing Students' Critical Reading Skills through the Integration of Critical Literacy Pedagogy and Teacher-Parent Collaboration Program - Anggraini, Gian Fitria; Sunendar, Dadang; Damayanti, Vismaia S; Musthafa, Bachrudin (Indonesian Journal on Learning and Advanced Education (IJOLAE), 2026)
This study investigates the effectiveness of an innovative instructional model that integrates critical literacy pedagogy with structured teacher–parent collaboration to enhance elementary students’ advanced critical reading skills. Grounded in the principles of critical literacy, the model extends literacy learning beyond the classroom by aligning school-based instruction with guided home literacy practices. The study responds to the urgent need to strengthen Indonesian students’ higher-order reading abilities in the context of information overload and persistent low literacy achievement. A quasi-experimental pre-test–post-test control group design was employed involving 37 fourth-grade students from a public elementary school in West Bandung Regency. The experimental group (n = 21) participated in the innovative collaborative literacy model, while the control group (n = 16) received conventional language instruction. The intervention was implemented through three stages problematization, cultural discussion, and social action—using thematic texts on bullying and environmental issues. Students’ critical reading was measured across six dimensions: interpretation, analysis, inference, evaluation, explanation, and self-regulation. Data were analyzed using independent sample t-tests. Results showed no significant pre-test differences between groups. However, post-test findings revealed a statistically significant improvement in the experimental group (p < 0.05) with medium normalized gain scores. Teachers demonstrated high pedagogical understanding, and parents showed adequate readiness, supporting effective implementation. These findings indicate that innovative family–school literacy integration can effectively advance critical reading development and offers a scalable approach to strengthening advanced literacy in primary education.